Community Participation and Ecotourism Development on Komodo Island: A Qualitative Case Study of Village-Level Engagement and Strategic Barriers - Ramdhan Kurniawan; Hendrian; Usep Suhud (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2026)
This study examines village community participation in ecotourism development on Komodo Island and identifies barriers that limit the transition from operational involvement to strategic authority. The analysis integrates Arnstein’s Ladder of Citizen Participation with community-based enterprise, empowerment, and collaborative governance perspectives. A qualitative case study was conducted in Komodo, Papagarang, and Mesa Villages from May to July 2025. Data were collected through 14 semi-structured interviews, two focus group discussions involving 6–8 participants per group, five participatory observation sessions, and document review. The data were analyzed manually using Braun and Clarke’s six-phase thematic analysis. The findings show that residents actively participate as tour guides, sea transportation providers, culinary entrepreneurs, and homestay operators. However, pricing, promotion, visitor scheduling, investment priorities, and destination planning remain largely controlled by external tour operators and public institutions. Limited managerial capacity, weak collective organization, inadequate infrastructure, unequal market access, dependence on external booking channels, and environmental pressures restrict local value capture. The study recommends formal community representation in destination governance, stronger village cooperatives, transparent pricing and booking systems, continuous business and conservation training, infrastructure improvement, and participatory monitoring. Active economic participation does not automatically produce strategic authority without institutional support and inclusive governance.